INTEGRATING CLINICAL SUPERVISION, ORGANIZATIONAL CULTURE, AND PSYCHOLOGICAL SAFETY TO STRENGTHEN TEACHERS' PEDAGOGICAL COMPETENCE: A MULTI-CASE STUDY IN INDONESIAN ELEMENTARY SCHOOLS - Akhmad Mundir; Andi Kristanto; Amrozi Khamidi (International Journal Multidisciplinary (IJMI), 2026)
teachers' pedagogical competence through a multidisciplinary integration of educational management, organizational culture, communication, and psychological safety. Although clinical supervision is often discussed as a technical cycle of pre-observation, classroom observation, and feedback, its effectiveness in schools is also shaped by the quality of professional relationships and institutional culture. Method: This study employed a qualitative embedded multi-case design in two Indonesian elementary education institutions with contrasting characteristics: SDN Kepanjen 2 Jombang, a public secular elementary school under the national education authority, and MIN 3 Jombang, a public Islamic elementary madrasah under the religious education authority. Data were collected through interviews, observation, documentation, rating-scale instruments, and member checking. The active clinical-supervision participants consisted of 17 of 37 teachers at SDN Kepanjen 2 Jombang and 15 of 32 teachers at MIN 3 Jombang. Results: The findings show that clinical supervision improves teachers' pedagogical competence when collegiality, collaboration, inquiry skills, and ethical conduct are supported by open communication, reflective culture, and psychological safety. SDN Kepanjen 2 showed stronger dialogic and participatory supervision, while MIN 3 Jombang maintained ethical and respectful supervision but was more constrained by hierarchical-relational norms and teacher reluctance. Novelty: The article contributes an integrated conceptual model of clinical supervision as a socio-professional process rather than a purely administrative or instructional mechanism.